(untitled) (Constructionism Conference Proceedings, 2025)
Come learn how to create microworlds which customize programming environments as a form of scaffolding for learners of specific needs, ages, or ability levels. Along the way, you will bring powerful ideas from Bruner, Perkins, and the Reggio Emilia approach to life in your teaching while developing your own computing fluency.